Achievement of treatment goals with canagliflozin in patients with type 2 diabetes mellitus: a pooled analysis of randomized controlled trials. (2nd November 2015) - Blonde, Lawrence; Woo, Vincent; Mathieu, Chantal; Yee, Jacqueline; Vijapurkar, Ujjwala; Canovatchel, William; Meininger, Gary
Abstract: Objective: To evaluate attainment of diabetes-related treatment goals with canagliflozin, a sodium glucose co-transporter 2 inhibitor, versus placebo in patients with type 2 diabetes mellitus (T2DM). Research design and methods: Data were pooled from four 26-week, placebo-controlled, Phase 3 studies of patients with T2DM ( N = 2313). Goal attainment with canagliflozin 100 and 300 mg versus placebo was evaluated in the overall population, and in subgroups based on age and sex, at baseline and Week 26. Clinical trial registration: ClinicalTrials.gov NCT01081834, NCT01106677, NCT01106625, NCT01106690. Main outcome measures: Proportion of patients achieving hemoglobin A1C (A1C) <7.0% and ≤6.5%, systolic blood pressure (SBP) <140 and <130 mmHg, diastolic blood pressure (DBP) <90 and <80 mmHg, low-density lipoprotein cholesterol (LDL-C) <100 mg/dL (2.6 mmol/L), high-density lipoprotein cholesterol (HDL-C) ≥40 mg/dL (1.0 mmol/L), and the composite endpoint of A1C <7.0%, BP <130/80 mmHg, and LDL-C <100 mg/dL (2.6 mmol/L) at baseline and Week 26, and proportion with body weight reduction ≥5% at Week 26. Results: At baseline, similar proportions of patients met diabetes-related treatment goals across groups. At Week 26, a greater proportion of patients achieved A1C, SBP, DBP, and HDL-C goals with canagliflozin 100 and 300 mg compared with placebo. More patients achieved body weight reduction of ≥5% with canagliflozin 100 and 300 mg versus placebo at Week 26. Fewer patients had LDL-C <100 mg/dL (2.6 mmol/L) at Week 26 with canagliflozin 100 and 300 mg versus placebo. Canagliflozin 100 and 300 mg also provided better attainment of the composite endpoint of A1C <7.0%, BP <130/80 mmHg, and LDL-C <100 mg/dL (2.6 mmol/L) compared with placebo. Attainment of diabetes-related treatment goals was generally similar regardless of age and sex. Key limitations of this analysis include the selection of specific treatment targets that may not be reflective of all patient experiences, the non-prespecified, post hoc nature of the analysis, and the short duration of studies included in the pooled population. Conclusion: Canagliflozin was associated with better attainment of diabetes-related treatment goals compared with placebo, and was generally well tolerated at 26 weeks.